Evaluación técnico financiera de la producción de aceite crudo partiendo del aprovechamiento de residuos plásticos post industriales tipo pp (polipropileno) a través del proceso de pirolisis en la empresa IPSA S.A.S. (2020)
The production of fuel from plastics has generated a significant advance in the field of renewable energy, achieving the emergence of a large number of high-tech facilities in different countries such as Germany, the United States, and England. The implementation of these technologies has yielded positive results in the management and use of plastic waste, since not only does the elimination of waste occur, but also its recovery. From the bibliographic review of the pyrolysis process in plastics, the most appropriate procedures were determined to carry out the physicochemical characterization of post-industrial polypropylene. Said analyzes consisted of determining the moisture content, ash content, volatile material, fixed carbon and thermogravimetric analysis. The measurements made it possible to establish the influence of these properties on the performance of the process. The results showed that percentages greater than 10% of moisture and ash content decrease oil production. Subsequently, the polypropylene pyrolysis process (post-industrial) was carried out at the laboratory level to obtain pyrolytic oil, from a factorial-type experimental design (22) with two replicates for each factor.